The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/ie303451s
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanical Properties of Consumer-Friendly PMMA Microcapsules

Abstract: Environmentally and consumer-friendly poly(methyl methacrylate) (PMMA) microcapsules were prepared on the basis of an in situ polymerization reaction to encapsulate perfume oil, which aims to be delivered to fabric surfaces via liquid detergents. Microcapsules with a narrow size distribution were produced using a membrane emulsification system; results were compared with a standard homogenization procedure. The shell thickness of microcapsules was found to increase with the polymerization reaction time, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 82 publications
2
31
0
1
Order By: Relevance
“…It is suggested that the shell grows inward with the reaction time, which the external section of the shell remains unchanged. This may also indicate the formed shell of microcapsules was porous that allowed MMA molecules to penetrate through it from the outside and to polymerize inside . The authors of the current work studied the mechanical properties of PMMA microcapsules filled with epoxy and mercaptan via nanoindentation method.…”
Section: Mechanical Properties Of Pmma Microcapsulesmentioning
confidence: 96%
See 1 more Smart Citation
“…It is suggested that the shell grows inward with the reaction time, which the external section of the shell remains unchanged. This may also indicate the formed shell of microcapsules was porous that allowed MMA molecules to penetrate through it from the outside and to polymerize inside . The authors of the current work studied the mechanical properties of PMMA microcapsules filled with epoxy and mercaptan via nanoindentation method.…”
Section: Mechanical Properties Of Pmma Microcapsulesmentioning
confidence: 96%
“…Micro/nanoencapsulation process of core materials using PMMA can be carried out by many techniques such as emulsion/miniemulsion polymerization, suspension polymerization, seeded polymerization, solvent evaporation from oil‐in‐water (o/w) emulsion (internal phase separation), surface‐initiated photopolymerization, and membrane emulsification . The emulsion polymerization and solvent evaporation are the most common techniques for the production of PMMA capsules, due to their simplicity in encapsulation of hydrophobic materials.…”
Section: Micro/nanoencapsulation Techniques Of Materials With Pmma Shellmentioning
confidence: 99%
“…Despite being costly and time consuming, this additional sample preparation step is advantageous for many microcapsule formulations. However, for microcapsules with a PMMA shell, for example, embedding in an acrylic resin causes the shells to dissolve (Pan, Mercadé-Prieto, York, Preece, & Zhang, 2013). In such situations, confocal laser scanning microscopy (CLSM) can be used.…”
Section: Structural Properties Of Microcapsulesmentioning
confidence: 99%
“…It is, however, worth remembering that the resolution is lower than that of TEM; this emphasizes that CLSM should be considered if interactions with the embedding medium cause shell degradation. There are reports of the use of CLSM in various microcapsule studies, in which the shell thickness was determined by examining the intensities across the mid-points of the resulting cross-sectional profiles (Lebedeva, Kim, & Vinogradova, 2004;Pan et al, 2013;Paramita, Iida, Yoshii, & Furuta, 2010;Tavera, Kadali, Bagaria, Liu, & Wong, 2009). …”
Section: Structural Properties Of Microcapsulesmentioning
confidence: 99%
“…Melaminle modifiye edilmiş üreformaldehit reçinesiyle yapılan çalışmada; karıştırma hızı ile kapsül boyutu arasında ters bir ilişki olduğu, yüksek karıştırma hızında kapsüllerin boyutlarının bir birine çok daha yakın olduğunu bulmuşlardır (Hu et al, 2009). Yapılan diğer bir çalışmada polimetilmetakrilatla elde edilmiş olan mikrokapsüllerin mekanik ve yapısal özellikleri incelenmiş ve elde ettikleri sonuçlardan birisi de karıştırma hızı ile kapsül boyutu arsındaki ters bir orantının olduğu sonucudur (Pan et al, 2013). M/F mol oranı 5/1'den 5/2.4 düştüğünde kapsül çeper kalınlığı 84 nm'den 308 nm çıktığını belirtmişlerdir (Long vd., 2009).…”
unclassified